Application potential of carbon nanomaterials in water and wastewater treatment: A review - Thines, R.; Mujawar, Mubarak; Nizamuddin, S.; Sahu, J.; Abdullah, E.; Ganesan, P. (2017)
© 2017 Taiwan Institute of Chemical EngineersAdvanced science and technology based on carbon-based nanomaterials is experiencing a rapid rate of change in the performance capabilities to substitute or serve as alternative approaches for the existing technologies. One of the major environmental concerns is the water pollution by the heavy metals. Heavy metals in water are the main preoccupation for many years because of the toxicity towards aquatic-life, human beings and also the environment. In the context of water and wastewater treatment, significant numbers of breakthroughs have been achieved to drive accelerated change for ceaseless capability improvements. In this contribution, the unique features of promising carbon-based nanomaterials that have generated tremendous interest among the material researchers are described along with their potential applications in water and wastewater treatment. Carbon-based nanomaterials stand out to be one of the highly efficient nanomaterials due to it is a vast availability and lower production cost compared to other nanomaterials. This paper critically reviewed the application of different type of carbon-based nanomaterials in water and wastewater treatment. The carbon nanomaterials role in adsorption, disinfection and membrane separation mechanisms that enable the applications are discussed. Advantages and limitations as well as barriers and research needs are highlighted. Challenges include technical hurdles, high cost, and environmental and health risk.